The effect of self efficacy on work engagement mediated by psychological well being in employed student - Buulolo, Delviana; Hardjo, Suryani; Aisyah, Siti (Jurnal Ilmiah Psikologi Terapan, 2025)
This study aims to analyze the effect of self-efficacy on work engagement with psychological well-being as a mediator in working students. The research sample was 216 students who were attending college at night and working full time, selected using purposive sampling technique. Data collection was carried out through a scale of self-efficacy, psychological well-being, and work engagement. The analysis used Structural Equation Modeling (SEM) method with SmartPLS software. The results showed that self-efficacy has a positive and significant effect on work engagement by 19% and on psychological well-being by 25%. Psychological well-being also positively and significantly affects work engagement by 44.3%. Additionally, psychological well-being mediates the relationship between self-efficacy and work engagement by 11.1%. Psychological well-being is proven to mediate the relationship between self-efficacy and work engagement. This shows that students with high levels of self-efficacy tend to have good psychological well-being, which in turn increases their work engagement. The practical implication of this research is the importance of increasing self-efficacy and psychological well-being to increase work engagement, especially in student workers. Educational institutions and companies are expected to design training programs that support the development of self-efficacy and psychological well-being of employees.